Epizootiologic survey of selenium and vitamin E concentrations in cattle to be slaughtered in Thessaloniki - CHRISTODOULOPOULOS (Γ. ΧΡΙΣΤΟΔΟΥΛΟΠΟΥΛΟΣ), G.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ), N.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), H.; PAPASTERIADIS (Α. ΠΑΠΑΣΤΕΡΙΑΔΗΣ), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
The purpose of this survey was the study of selenium (Se) and vitamin E (vit. E) concentrations in cattle to be slaughtered in the area of Thessaloniki. For this purpose, research samples of blood and liver were collected from 205 cattle brought to different slaughter-houses of Thessaloniki. Out of the 205 cattle to be slaughtered, 78% presented deficient concentration of Se in liver (0,110-0,600 μg/g DM), 17% marginally deficient concentration(0,601-0,900 μg/g DM) and only 5% normal concentration (0,901-1,512 μg/g DM). Regarding vit. E, only 5% out of the 205 cattle to be slaughtered presented deficient concentration in liver (<5 μg/g WW). It is concluded from the above that, in Thessaloniki, a significant percentage of cattle run the risk of Se deficiency diseases. On the contrary, the case of vit. E deficiency, should be regarded as improbable for these animals.